2021
DOI: 10.51847/ojxvscmh9y
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine: Education and Occupation Influences Its Practice among Residents of Port Harcourt, South-South Nigeria

Abstract: Herbal medicine plays an important role in Nigerian society based on its increased patronage. It encompasses the use of naturally occurring, plant-derived substances which are employed to prevent, manage, or treat illnesses. This study was conducted to assess the knowledge, attitude, and practice (KAP) of herbal medicine among the residents of Port Harcourt, Rivers State, Nigeria. A descriptive cross-sectional survey was carried out on 280 residents using self-administered questionnaires comprising demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Therefore, data was not differentiated in terms of gender, age, education and occupation. In contrast, however, several studies have indicated that gender (Bano et al 2014;Wiryono et al 2019), age (Bano et al 2014;Pérez-Nicolás et al 2017;Wiryono et al 2019), education (Bano et al 2014;Pérez-Nicolás et al 2017;Rahayu et al 2020) and occupation (Moke et al 2021;Rahayu et al 2020) do influence the transmission of traditional knowledge about medicinal plants' therapeutic uses in many ethnic communities.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, data was not differentiated in terms of gender, age, education and occupation. In contrast, however, several studies have indicated that gender (Bano et al 2014;Wiryono et al 2019), age (Bano et al 2014;Pérez-Nicolás et al 2017;Wiryono et al 2019), education (Bano et al 2014;Pérez-Nicolás et al 2017;Rahayu et al 2020) and occupation (Moke et al 2021;Rahayu et al 2020) do influence the transmission of traditional knowledge about medicinal plants' therapeutic uses in many ethnic communities.…”
Section: Discussionmentioning
confidence: 97%
“…Medicinal plants have also been reported to be effective in the management of diabetic state (Asiwe et al, 2023;Moke et al, 2023a).…”
Section: Pharmacological Management Of Diabetes Mellitusmentioning
confidence: 99%
“…According to Belachew et al, 23.83% of respondents believe complementary and alternative treatment is more beneficial than traditional therapy [19]. Nalini et al informed that Malaysian consumers have a favorable attitude toward medicinal plant intake [22,23]. Furthermore, El-Olemy et al stated that 46% of respondents in their study feel that complementary and traditional medicine is safe and medically effective, with 87% of those who have previously used complementary and traditional medicine have not experienced any complications [16].…”
Section: Attitudes Toward Herbal Medicinementioning
confidence: 99%